Selling Shakespeare biography, bibliography, and the book trade - Hooks, Adam G. (Cambridge University Press, 2016)
Selling Shakespeare tells a story of Shakespeare's life and career in print, a story centered on the people who created, bought, and sold books in the early modern period. The interests and investments of publishers and booksellers have defined our ideas of what is 'Shakespearean', and attending to their interests demonstrates how one version of Shakespearean authorship surpassed the rest. In this book, Adam G. Hooks identifies and examines four pivotal episodes in Shakespeare's life in print: the debut of his narrative poems, the appearance of a series of best-selling plays, the publication of collected editions of his works, and the cataloguing of those works. Hooks also offers a new kind of biographical investigation and historicist criticism, one based not on external life documents, nor on the texts of Shakespeare's works, but on the books that were printed, published, sold, circulated, collected, and catalogued under his name